ANALISIS ASPHALT WEARING COURSE AC-WC DENGAN BAHAN TAMBAH TILE CERAMIC WASTE AND RED BRICK WASTE UNTUK PERKERASAN JALAN - Alpin Hartanto; Defa Kuswanto; Juny Andry Sulistyo (Pondasi, 2025)
ANALYSIS OF ASPHALT WEARING COURSE AC-WC WITH ADDED MATERIALS OF WASTE CERAMIC TILE AND WASTE RED BRICK FOR ROAD PAVEMENTABSTRAKThis study aims to evaluate the effect of adding Tile Ceramic Waste and Red Brick Waste as additives on the characteristics of the Asphalt Concrete-Wearing Course (AC-WC) mixture. The use of these wastes aims to reduce environmental impact while improving road pavement performance.The research was conducted at the Road Pavement Laboratory of the Faculty of Engineering, Unissula, using the Marshall test method. The mixture variations included 0%, 3%, 6%, and 8% of Tile Ceramic Waste and 0%, 2%, and 4% of Red Brick Waste. Tested parameters included stability, flow, density, VMA, VIM, VFA, and Marshall Quotient.The results showed that the addition of both wastes significantly affected stability and other Marshall parameters. The optimum composition resulted in a stability value of 1575.05 kg, VIM 3.22%, VMA 15.82%, VFA 79.65%, and a Marshall Quotient of 218.76 kg/mm. This research demonstrates that ceramic and red brick waste can be effectively utilized as additives in AC-WC asphalt mixtures.Keywords: Asphalt Concrete-Wearing Course, Tile Ceramic Waste, Red Brick Waste, Marshall Test, Road Pavement ANALISIS ASPHALT WEARING COURSE AC-WC DENGAN BAHAN TAMBAH TILE CERAMIC WASTE AND RED BRICK WASTE UNTUK PERKERASAN JALANABSTRAKPenelitian ini bertujuan untuk mengevaluasi pengaruh penambahan limbah Tile Ceramic Waste dan Red Brick Waste sebagai bahan tambah (additive) terhadap karakteristik campuran Asphalt Concrete-Wearing Course (AC-WC). Pemanfaatan limbah ini bertujuan untuk mengurangi dampak lingkungan sekaligus meningkatkan performa perkerasan jalan.Penelitian dilakukan di Laboratorium Perkerasan Jalan Fakultas Teknik Unissula dengan metode uji Marshall. Variasi campuran menggunakan limbah Tile Ceramic Waste sebesar 0%, 3%, 6%, dan 8%, serta limbah Red Brick Waste sebesar 0%, 2%, dan 4%. Parameter yang diuji meliputi stabilitas, kelelehan (flow), densitas, VMA, VIM, VFA, dan Marshall Quotient. Hasil penelitian menunjukkan bahwa penambahan kedua limbah memberikan pengaruh signifikan terhadap nilai stabilitas dan parameter Marshall lainnya. Komposisi optimum menghasilkan nilai stabilitas sebesar 1575,05 kg, VIM 3,22%, VMA 15,82%, VFA 79,65%, dan Marshall Quotient 218,76 kg/mm. Penelitian ini menunjukkan bahwa limbah keramik dan bata merah dapat dimanfaatkan sebagai bahan tambah yang efektif untuk campuran aspal AC-WC.Kata Kunci: Asphalt Concrete-Wearing Course, Tile Ceramic Waste, Red Brick Waste, Marshall Test, Perkerasan Jalan